L'Imaginaire du Complot Discours d'extrême droite en France et aux Etats-Unis - Jamin, Jérôme (IMISCoe Dissertations, 2009)
This book explores the importance of conspiracy rhetoric within populist and far right speeches in Europe and the United States. It shows how a "New World Order" plot give to populist and far right parties an opportunity to develop a rhetoric based on the rescue of democracy despite their obvious rejection of the values and principles which set up democracy.